Cover crops influence above- and belowground invertebrates in a northern grain field - Thitz, Paula; Tiusanen, Mikko; Cappelli, Seraina Lisa; Gerin, Stephanie; Shrestha, Rashmi; Hagner, Marleena; Heinonsalo, Jussi; Laine, Anna-Liisa; Mikola, Juha (Elsevier, 2026)
Maintaining vegetation diversity through cover crops could counteract the decreasing soil carbon and biodiversity in intensive monoculture farming. To investigate how cover crops influence the abundance and trophic structure of invertebrates and soil inorganic N availability (an example of an important soil function), barley (Hordeum vulgare) was grown with up to eight undersown cover crops (Lolium multiflorum, Phleum pratense, Trifolium hybridum, T. repens, T. pratense, Medicago sativa, Festuca arundinacea, Cichorium intybus) selected to include N2-fixers, non-N2-fixers and shallow- and deep-rooted species. Soil fauna (nematodes, enchytraeids and earthworms), slugs, and arthropods living on soil surface, vegetation, and barley were sampled, and soil inorganic N availability measured in summer and/or autumn in the second and third year of the experiment. Cover crops increased the abundance of aboveground and belowground invertebrates compared to barley monoculture. The proportion of predatory arthropods increased, suggesting that cover crops improved the potential for biological control. The cover crop functional traits that were missing in barley monoculture (N2-fixation and deep roots) had selective effects. For example, legumes increased soil inorganic N availability and the abundance of aboveground herbivores, while deep-rooted species benefited earthworms. The species richness of cover crops did not affect invertebrates or soil N. Our results suggest that adding plant diversity to agroecosystems with cover crops supports invertebrate communities and their ecosystem functions. Additionally, significant effects on invertebrate-mediated ecosystem functions such as biological control may already be achieved at low levels of added vegetation diversity.
Keywords: agroecosystem; biological control; cover crop; invertebrate; monoculture; soil N; vegetation diversity